Detection of Paralytic Shellfish Toxins in Mussels and Oysters Using the Qualitative Neogen Lateral-Flow Immunoassay: An Interlaboratory Study. (23rd November 2019) - Dorantes-Aranda, Juan José; Tan, Jessica Y C; Hallegraeff, Gustaaf M; Campbell, Katrina; Ugalde, Sarah C; Harwood, D Tim; Bartlett, Jill K; Campàs, Mònica; Crooks, Steven; Gerssen, Arjen; Harrison, Keith; Huet, Anne-Catherine; et al.
Abstract: Paralytic shellfish toxins (PSTs) in bivalve molluscs represent a public health risk and are controlled via compliance with a regulatory limit of 0.8 mg saxitoxin (STX)⋅2HCl equivalents per kilogram of shellfish meat (eq/kg). Shellfish industries would benefit from the use of rapid immunological screening tests for PSTs to be used for regulation, but to date none have been fully validated. An interlaboratory study involving 16 laboratories was performed to determine the suitability of the Neogen test to detect PSTs in mussels and oysters. Participants performed the standard protocol recommended by the manufacturer and a modified protocol with a conversion step to improve detection of gonyautoxin 1&4. The statistical analysis showed that the protocols had good homogeneity across all laboratories, with satisfactory repeatability, laboratory, and reproducibility variation near the regulatory level. The mean probability of detection (POD) at 0.8 mg STX⋅2HCl eq/kg using the standard protocol in mussels and oysters was 0.966 and 0.997, respectively, and 0.968 and 0.966 using the modified protocol. The estimated LOD in mussels was 0.316 mg STX⋅2HCl eq/kg with the standard and 0.682 mg STX⋅2HCl eq/kg with the modified protocol, and 0.710 and 0.734 mg STX⋅2HCl eq/kg for oysters, respectively. The Neogen test may be acceptable for regulatory purposes for oysters in accordance with European Commission directives in which the standard protocol provides, at the regulatory level, a probability of a negative response of 0.033 on 95% of occasions. Its use for mussels is less consistent at the regulatory level due to the wide prediction interval around the POD.